2019
DOI: 10.1108/ijoem-08-2018-0443
|View full text |Cite
|
Sign up to set email alerts
|

The stability of demand for money in the proposed Southern African Monetary Union

Abstract: Purpose The purpose of this paper is to investigate the stability of demand for money in the proposed Southern African Monetary Union (SAMU). Design/methodology/approach The study uses annual data for the period 1981 to 2015 from ten countries making-up the Southern African Development Community. A standard function of demand for money is designed and estimated using a bounds testing approach to co-integration and error-correction modeling. Findings The findings show divergence across countries in the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
2
9
0
Order By: Relevance
“…namely: Gambia, Burkina Faso, Sierra Leon, Mauritania and Liberia have stability in their money demand functions whilst the remaining eleven (11) exhibited partial stability. These results are consistent with the findings of Asongu et al (2019a) who also found significant divergence in the stability of money demand function among Southern Africa development countries. The evidence from these test of stability especially among the remaining eleven (11) countries points to the fact that despite the conscious efforts of most countries in west Africa through policies and programs such as the Economic Recovery Program (ERP), Structural Adjustment Program (SAP) and all the policies towards financial liberalization and financial deepening; eleven (11) of these are still experiencing significant instability.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…namely: Gambia, Burkina Faso, Sierra Leon, Mauritania and Liberia have stability in their money demand functions whilst the remaining eleven (11) exhibited partial stability. These results are consistent with the findings of Asongu et al (2019a) who also found significant divergence in the stability of money demand function among Southern Africa development countries. The evidence from these test of stability especially among the remaining eleven (11) countries points to the fact that despite the conscious efforts of most countries in west Africa through policies and programs such as the Economic Recovery Program (ERP), Structural Adjustment Program (SAP) and all the policies towards financial liberalization and financial deepening; eleven (11) of these are still experiencing significant instability.…”
Section: Resultssupporting
confidence: 92%
“…Based on the relevant literature on the stability of money demand function and co-integration method (Bahmani-Oskooee & Gelan, 2009;Asongu et al, 2019a); the Auto-regressive Distributed lag model (ARDL) is adopted due to its consistent features with the data. The ARDL's appropriateness is based on the fact that it ideal when the series used are made of variables integrated of order zero I(0) and order I(1).…”
Section: Methodsmentioning
confidence: 99%
“…As a precautionary measure and in order to ascertain the suitability of our choice of methodology based on the nature of each data, building on contemporary literature (Asongu 2014;Asongu et al 2019b), a stationarity test was conducted on each variable using the Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests and the results are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Time series data are a collection of random variables at given point in time and they are generally seen to be stationary if the mean and variance are constant over time and the value of the covariance does not depend on the actual time in which they are computed (Box et al 2015). Two major approaches were followed to conduct the unit root test for the variables following some contemporary studies (Haseeb et al, 2018;Asongu et al, 2019;Onıfade et al, 2020a). Firstly, we applied the Augmented Dickey-Fuller (ADF, 1981) approach to test for the unit root as follows:…”
Section: Unit Root Testmentioning
confidence: 99%